REFLECTIONS OF DR. B.R AMBEDKAR’S IDEA OF SOCIAL JUSTICE - Ahmad Lone, Shabir (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Dr. B. R. Ambedkar is revered as a hero for his role in advancing equality. Bhimrao Ramji Ambedkar was an instrumental figure in the formation of our nation's constitution and was one of the principal authors of it. He made it illegal to discriminate against those who were considered to be of a lower caste or to be untouchable, and he worked toward establishing equality among the citizens of our nation. He stated that he had faith in a community that could support the ideals of friendship, equality, and fraternity. However, in the early days of our nation, a man who had done so much for our country had been subjected to numerous cruelties because of his caste. Dr. Bhimrao Babasaheb Ramji Ambedkar was a renegade who challenged the social order in which the contradiction of caste and class had been apparent for years. His egalitarian philosophy was "one man, one value," and it was based on the belief that everyone should be treated equally. Dr. Ambedkar worked hard to change the pre-existing social order based on caste and class, and he strove to plant the seed of social justice. He accomplished this by lobbying for a wide range of causes, including the plight of the caste system and untouchability, human rights, labour rights, women's rights, and, most crucially, Indian politics. Because he was born into a mahar family in the state of Maharashtra, he was subjected to the humiliations and discrimination that came with being an untouchable. According to B. R. Ambedkar, social justice is a method for constructing an ideal society or a society that is just. According to him, a just society is one that does not practice caste, is founded on the ideals of social justice, and incorporates all three of the following elements: liberty, equality, and fraternity. Ambedkar's vision for the perfect society is underpinned by a commitment to a pair of core values. The purpose of the study is to describe and analyze the concept of social justice that was conceived of by B.R. Ambedkar, who was the architect of the Indian constitution.